Examining Physician Interactions with Disease Advocacy Organizations. Issue 4 (2nd October 2019) - Horrow, Caroline; Pacyna, Joel E.; Cosenza, Carol; Sharp, Richard R.
Abstract: Disease advocacy organizations (DAOs) have traditionally focused on raising awareness of rare diseases, providing educational resources to patients, and supporting patients and families. Previous research has described how scientists collaborate with DAOs, but few empirical data are available regarding the extent to which physicians interact with DAOs and how those interactions impact patient care. We conducted a national survey of 230 board-certified pediatric neurologists to assess their engagement with DAOs and their beliefs about the impact of DAOs on patient care. In that context, we evaluated a set of 24 items describing interactions between physicians and DAOs. Exploratory factor analysis produced a 19-item model capturing four types of physician–DAO engagement: (1) accessing or distributing DAO-produced materials (6 items, alpha = 0.80); (2) consulting on DAO activities (5 items, alpha = 0.81); (3) collaborating with DAOs on research activities (6 items, alpha = 0.80); and (4) co-producing scholarly materials with DAOs (2 items, alpha = 0.80). Our data indicate that physicians engage with DAOs in more frequent and diverse ways than has been previously reported. Almost all physicians in our sample had interacted directly with a DAO in some way, from low-effort activities such as visiting a DAO's website to deeper forms of engagement including coauthoring journal articles. These findings may provide a framework for bioethicists to characterize the nature and extent of physician interactions with advocacy organizations, which is critical for evaluating the ethical implications of physician–DAO relationships.